Human perceptions and attitudes in the production of alfalfa under irrigation in La Pampa, Argentina (Semiárida, 2021)
A case of wild species management. In La Pampa province, tucotucos (Ctenomys azarae) cause economic losses in alfalfa productive systems under pressurized irrigation. As a management strategy, biological control with birds of prey is promoted. Since this problem is based on humanwildlife interaction, the study of social aspects is paramount. The aim of this paper was to study the attitudes and perceptions of the social component in order to define level of damage and selected method efficiency to control tucotucos. Workers were surveyed to define the productive problem and determine their level of knowledge about tucotucos and birds of prey. Moreover, the attitudes of rural workers during the study and the execution of the biological control project were documented. The damage caused by tucotucos represents between 0.6 and 7 % of the annual earnings by the selling of alfalfa big bales. The damage is mainly quantified in the cost and number of harvesting machinery blades that have to be replaced and the reduction of the big bales quality. Workers see biological control as an opportunity to face the problem and recognize their ecological role. Social participation in the project improves the understanding of the biological intervening situation and favors the application of management practices.
Keywords: agriculture; biological control; Ctenomys; damage; social component